Unpaulinische Stilmerkmale im 2. Thessalonicherbrief?: Die stilkritischen Argumente Wolfgang Trillings in statistischer Perspektive = Non-Pauline Stylistic Features in 2 Thessalonians?: Wolfgang Trilling’s Style-Critical Arguments from a Statistical Perspective - Baum, Armin Daniel (Novum Testamentum, 2026)
The stylistic research conducted by Wolfgang Trilling and Daryl Schmidt on 2 Thessalonians has led numerous authors of New Testament introductions and commentaries to conclude that the style of this epistle differs significantly from that of the genuine Pauline epistles. However, a comprehensive statistical examination of the evidence cited by Trilling and Schmidt demonstrates that there are close analogies to all these stylistic features in Paul’s undisputed letters. Therefore, the argument for the post-Pauline origin of 2 Thessalonians cannot be based on non-Pauline elements of its style.